1988
DOI: 10.1172/jci113748
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1-dependent paracrine granulopoiesis in chronic granulocytic leukemia of the juvenile type.

Abstract: Marrow and peripheral blood cells from nine children with juvenile chronic granulocytic leukemia (JCGL) demonstrated intense (94±16% maximum) spontaneous granulocyte/macrophage colony growth but cells from five children with the adult variety of CGL did not. This unusual pattern of colony growth depended upon a stimulatory protein(s) produced by mononuclear phagocytes. No GM-CSA activity was found in any chromatofocused fraction of JCGL monocyte-conditioned media but an activity that induced GM-CSA in umbilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 36 publications
3
26
1
3
Order By: Relevance
“…Thus, the results suggest that a highly purified population of JCML CD34 + can "self-start" and form colonies in keeping with an autocrine growth pattern. Our data differ from previous studies by others that showed impaired spontaneous JCML colony formation after adherent cell depletion [12,38]. Their studies were performed on light density cells and ours on highly purified CD34 + cells.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, the results suggest that a highly purified population of JCML CD34 + can "self-start" and form colonies in keeping with an autocrine growth pattern. Our data differ from previous studies by others that showed impaired spontaneous JCML colony formation after adherent cell depletion [12,38]. Their studies were performed on light density cells and ours on highly purified CD34 + cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Within these mixed populations of cells, there must be a subpopulation of JCML progenitors that accounts for the abnormal proliferative properties [1][2][3][4][5][6][7][8][9][10][11][12] of the monocyte-macrophage progeny. Our goal is to identify and characterize these JCML progenitors in order to ask fundamental questions about the biology of this aggressive form of leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Erythroid and megakaryocytic series can be decreased, either due to the granulocytic hypercellularity and subsequent 'crowding out' phenomenon or due to cytokine suppression. 14,29 If the clinician is able to obtain blood before the need for red blood cell transfusions, a hemoglobin electrophoresis can be useful in helping to establish the diagnosis, as greater than 50% of JMML patients will demonstrate a reversion to fetal red blood cell characteristics, including (1) increased levels of hemoglobin F, even when corrected for age, (2) low carbonic anhydrase levels and (3) expression of the i antigen. 30 It should be emphasized that elevated fetal hemoglobin levels are not necessary for a diagnosis of JMML, due to the fact that at least one-third of confirmed JMML diagnoses have normal fetal hemoglobin levels.…”
Section: Jmmlflaboratory Findingsmentioning
confidence: 99%
“…In the 1980s, it was most commonly known as juvenile chronic myelogenous leukemia, but other names ascribed to this disease in the past included juvenile chronic granulocytic leukemia, chronic and subacute myelomonocytic leukemia, CMML of childhood, infantile monosomy 7 and monosomy 7 syndrome. [10][11][12][13][14][15] Some argued that it should be classified as a childhood form of MDS. 16 But, similar to 'adult-type' CMML, this disease clearly had some characteristics of an MPD.…”
Section: Introduction To Chronic Myelomonocytic Leukemiamentioning
confidence: 99%
“…22 Activation of TLR pathways in macrophages induces production of other inflammatory cytokines, including interleukin 1b (IL-1b), [23][24][25] which is known to promote tumor progression and metastasis. 26,27 Expression of IL-1b, like TNF-a, is known to be dependent on the activity of the global stress responsive p38 mitogen-activated protein kinase (MAPK) signal transduction pathway. 28 Therefore, in light of our prior studies and the work of others confirming that TNF-a is a potent endogenous suppressor of normal hematopoietic progenitor and stem cell activity in mice, [11][12][13][14][15] we reasoned that FA marrow progenitors and stem cells might also be hypersensitive to IL-1b and that TLR activation might induce the overproduction of both TNF-a and IL-1b by FA mononuclear phagocytes.…”
Section: Introductionmentioning
confidence: 99%